Regulated and Non-Regulated Emissions from Euro 6 Diesel, Gasoline and CNG Vehicles under Real-World Driving Conditions - Ricardo Suarez-Bertoa; Martin Pechout; Michal Vojtíšek; Covadonga Astorga (Atmosphere, 2020)
The transport sector is one of the main sources air pollutants. Different exhaust after-treatment systems have been implemented over the years to control the emissions of criteria pollutants. However, while reducing the emissions of the target compounds these systems can lead to the emissions of other pollutants and/or greenhouse gases such as NH3 or N2O. Following the implementation of the Real Driving Emissions (RDE) test procedure in the EU, vehicles have been equipped with more complex after-treatment configurations. The impact that these technologies may have on the emissions of non-regulated pollutants during real-world driving have not been evaluated until now. In the current study we present the on-road emissions of a series of non-regulated pollutants, including NH3, N2O, CH4 and HCHO, measured with a portable FTIR from a series of Euro 6d, Euro 6c and Euro 6d-TEMP, gasoline diesel and compressed natural gas (CNG) vehicles during real-world testing. The obtained results show that it is possible to measure N2O, NH3, CH4 and HCHO during on-road operation. The results also highlight the importance of the measurement of the emissions of these pollutants during real-world driving, as the emissions of NH3 (a particulate matter precursor) and those of N2O and CH4 (green-house gases) can be high from some vehicle technologies. NH3 emissions were up to 49 mg/km for gasoline passenger cars, up to 69 mg/km for the CNG light-commercial vehicle and up to 17 mg/km a diesel passenger car equipped with a selective catalytic reduction system (SCR). On the other hand, N2O and CH4 emissions accounted for up to 9.8 g CO2 eqv/km for a diesel passenger car equipped with a combination of diesel oxidation catalysts (DOC), lean NOx traps (LNT), SCR and possibly an ammonia slip catalyst ASC.